Method and system for detecting and evaluating aging of nylon 6 in marine environment
By integrating a composite conductive film and an aging-responsive color-changing material into a nylon 6 matrix, a comprehensive aging index (CAI) is constructed, which solves the problems of convenience and real-time performance in nylon 6 aging detection in marine environments. This enables simple and rapid aging assessment and is applicable to nylon 6 components in marine engineering.
Patent Information
- Application Number
- CN202511105376.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-07
- Publication Date
- 2025-10-21
AI Technical Summary
Existing technologies are insufficient for quickly and conveniently monitoring the aging of Nylon 6 in marine environments, especially in applications such as offshore wind power and ships, where traditional testing methods and equipment are complex, expensive, and difficult to implement.
The Comprehensive Aging Index (CAI) assessment method, which normalizes color and resistance parameters, is used to achieve real-time and intuitive aging detection by integrating a composite conductive film and aging-responsive color-changing material into a nylon 6 matrix. It provides dual signal output by combining color gradient indication and easy electronic reading.
It enables convenient and real-time aging testing of Nylon 6, reduces equipment complexity and cost, improves the feasibility of on-site testing, and provides a new technical solution for life prediction and preventive maintenance.
Smart Images

Figure QLYQS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of engineering plastic detection, and in particular to an aging detection and evaluation method and system for nylon 6 in a marine environment. Background Art
[0002] As an important engineering plastic, nylon 6 is widely used as a structural component and functional assembly in marine engineering, shipbuilding, offshore wind power, and other fields due to its excellent mechanical properties, chemical corrosion resistance, and processing properties. However, under the influence of complex marine environmental factors, nylon 6 will undergo a series of aging phenomena, among which color change is one of the most intuitive and earliest signs of aging. Studies have shown that after five years of exposure to tropical marine climates, the color of glass fiber reinforced nylon 6 samples undergoes significant changes, mainly manifested in a decrease in lightness (L value) and a change in hue. This is the result of the combined effects of factors such as surface stress cracking, floating fibers, salt spray enrichment, and the oxidation of methylene to form chromophores.
[0003] Currently, the main technical means of monitoring the color change of nylon 6 in the marine environment include: 1. Colorimeter detection: Regular sampling and measurement of surface color difference ΔE value, which requires specialized equipment and sample preparation; 2. UV-visible spectroscopy: Analysis of chromophore formation through changes in absorption spectra, which requires expensive equipment and complex operation; 3. Infrared spectroscopy (ATR-FTIR): Monitoring amide bond (1645cm - ¹) and other characteristic peak changes, requiring laboratory conditions. 4. Visual inspection: Relies on human experience, is highly subjective, and lacks quantification. These methods generally suffer from poor real-time performance, require sampling, and involve complex or costly equipment, making them difficult to meet the demands of rapid on-site assessments. This is particularly true in applications such as offshore wind power and ships, where nylon 6 components are often installed in inaccessible locations, making traditional inspection methods challenging. Summary of the Invention
[0004] To address the shortcomings and deficiencies of traditional detection methods, the present invention provides a method for detecting and evaluating nylon 6 aging in marine environments. By integrating a specially designed surface aging-responsive color-changing material and a composite conductive film into the nylon 6 matrix, this method enables real-time, intuitive, and efficient detection of aging processes. This method not only overcomes the complexity and expense of traditional fiber optic spectrometers and other equipment, but also significantly enhances the convenience of on-site testing through dual signal outputs: color gradient indication and simple electronic readout. It can also meet the detection needs of diverse application scenarios, providing a novel technical solution for lifespan prediction and preventative maintenance of nylon 6 components in marine engineering.
[0005] Another object of the present invention is to provide a nylon 6 aging detection and evaluation system in a marine environment. This system not only solves the problem of the complexity and high cost of traditional equipment such as fiber optic spectrometers, but also greatly improves the convenience of on-site detection through dual signal output of color gradient indication and simple electronic readout, providing a new technical solution for life prediction and preventive maintenance of nylon 6 components in marine engineering.
[0006] In order to further achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for detecting and evaluating nylon 6 aging in a marine environment, wherein the method normalizes color and resistance parameters to construct a comprehensive aging index (CAI), which is expressed as:
[0008] (1)
[0009] Where, , represents the weight coefficient, , ; represents the color difference threshold, =5; represents the resistance change threshold, ; Indicates the resistance change; Indicates the initial resistance value;
[0010] The evaluation criteria for CAI are: CAI < 0.5: mild aging; 0.5 ≤ CAI < 1.0: moderate aging; CAI ≥ 1.0: severe aging.
[0011] A system for implementing the aforementioned nylon 6 aging detection and evaluation method in a marine environment includes nylon 6 as a core layer, an aging-responsive color-changing material as a surface layer, and an intermediate layer located between the core layer and the surface layer, wherein the core layer is pure nylon 6 or glass fiber reinforced nylon 6, which is used to maintain mechanical properties; the intermediate layer has a thickness of 200-250μm, and the composite conductive film is transferred to 0.2mm below the surface of the nylon 6 component by hot pressing; the surface layer has a thickness of 0-200μm, which is achieved by spraying a solution of the aging-responsive color-changing material.
[0012] Optionally, the aging-responsive color-changing material is composed of the following components: an oxidation indicator, a nanocarrier, and a stabilizer, wherein: the oxidation indicator is an alkaline aqueous solution of tetramethyl-p-phenylenediamine and potassium ferrocyanide; the nanocarrier is mesoporous silica nanoparticles; and the stabilizer is a hindered amine light stabilizer.
[0013] Preferably, the pore size of the silica nanoparticles is 3-5 nm.
[0014] Furthermore, the preparation method of the alkaline aqueous solution of tetramethyl-p-phenylenediamine and potassium ferrocyanide is as follows: potassium ferrocyanide and tetramethyl-p-phenylenediamine are dissolved in the alkaline aqueous solution in sequence, the concentration of potassium ferrocyanide is 0.2 mol / L, the concentration of tetramethyl-p-phenylenediamine is 0.2-0.4 mol / L, the reaction temperature is normal room temperature, and the reaction time is 1-3 hours.
[0015] Furthermore, the preparation method of the aging-responsive color-changing material comprises the following steps:
[0016] Step 1: Using mesoporous silica as a carrier and loading an oxidation indicator: Mesoporous silica nanoparticles with a pore size of 3-5 nm are immersed in an alkaline aqueous solution of tetramethyl-p-phenylenediamine and potassium ferricyanide, and ultrasonically dispersed for 15-20 minutes. The mixture is allowed to stand for 2 hours to allow adsorption equilibrium, and then vacuum-dried at 60°C to remove the solvent, thereby obtaining nanoparticles loaded with the oxidation indicator.
[0017] Step 2, raw material mass ratio: alkaline aqueous solution of tetramethyl-p-phenylenediamine and potassium ferrocyanide: 100 parts; silica loaded with oxidation indicator: 3-5 parts; hindered amine light stabilizer: 0.5-2 parts;
[0018] Step 3, dehydration: add alkaline aqueous solution of tetramethyl-p-phenylenediamine and potassium ferrocyanide and hindered amine light stabilizer into the reaction kettle, dehydrate under negative pressure at 110-120°C for 5-20 minutes, and stir at 200-300 rpm;
[0019] Step 4: Mixing: Add the silica loaded with the oxidation indicator into the kettle and stir for 2 minutes until the mixture is uniform.
[0020] Furthermore, the thickness of the aging-responsive color-changing material is 0-200 μm, and the addition amount is 0.3-0.8 wt%; when nylon 6 undergoes oxidative aging, the color of the material will gradually change from white to blue, and the color difference ΔE reaches 15-25, far exceeding the threshold ΔE>3 that can be identified by the naked eye.
[0021] Optionally, the base material of the composite conductive film is carbon nanotubes, and the thickness of the composite conductive film is 50 μm.
[0022] Furthermore, the nanotube is one of multi-walled carbon nanotube, thin-walled carbon nanotube and single-walled carbon nanotube.
[0023] Preferably, the carbon nanotubes are thin-walled carbon nanotubes with an outer diameter of 3-5 nm, a length of 5-30 μm, a purity of >90%, and a conductivity of >100 S / cm.
[0024] Compared with the prior art, the present invention has the following outstanding advantages:
[0025] 1. Convenient detection: Intuitive color changes and simple electronic readouts replace complex spectral equipment, reducing detection time from hours to minutes.
[0026] 2. Real-time monitoring capability: The built-in composite conductive film can provide continuous aging data without stopping the machine for sampling, solving the hysteresis problem of traditional methods.
[0027] 3. Process compatibility: Conductive film and color-changing material are applied to the surface of nylon 6 using processes such as hot pressing and spraying to minimize the impact on the mechanical properties of the nylon 6 base material.
[0028] 4. Comprehensive evaluation method: Combining the dual aging response mechanisms of chemical color development and physical conductive materials, a comprehensive evaluation method for nylon 6 aging is formed. The two types of monitoring data can be mutually verified, and the evaluation results are more scientific and reliable. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0030] Example 1:
[0031] A nylon 6 aging detection and evaluation system for use in marine environments comprises nylon 6 as a core layer, an aging-responsive color-changing material as a surface layer, and an intermediate layer between the core and surface layers. The core layer is pure nylon 6 or glass-fiber reinforced nylon 6, and is used to maintain mechanical properties. The intermediate layer has a thickness of 200-250 μm, and a grid-shaped composite conductive film is transferred to 0.2 mm below the surface of the nylon 6 component by hot pressing. The surface layer has a thickness of 0-200 μm, and is achieved by spraying a solution of the aging-responsive color-changing material.
[0032] In this embodiment, an aging-responsive color-changing material is designed to address the color change caused by oxidation of nylon 6 in a marine environment. The aging-responsive color-changing material is composed of the following components: an oxidation indicator, a nanocarrier, and a stabilizer, wherein:
[0033] The oxidation indicator is a composite system of tetramethyl-p-phenylenediamine (TMPD) and potassium ferricyanide, specifically an alkaline aqueous solution of tetramethyl-p-phenylenediamine and potassium ferricyanide. When nylon 6 undergoes oxidation, TMPD is oxidized to a deep blue Wurster salt, a significant and irreversible color change. This system is particularly sensitive to carbonyl compounds generated by the oxidation of amide bonds in nylon 6. The alkaline aqueous solution of tetramethyl-p-phenylenediamine and potassium ferricyanide is prepared by sequentially dissolving potassium ferricyanide and TMPD in an alkaline aqueous solution, such as a 0.5-0.6 mol / L KOH solution. The concentration of potassium ferricyanide is 0.2 mol / L, and the concentration of TMPD is 0.2-0.4 mol / L. The reaction temperature is room temperature, and the reaction time is approximately 1-3 hours. Both TMPD and potassium ferricyanide are commercially available products.
[0034] The nanocarrier uses mesoporous silica nanoparticles (pore size 3-5nm) to load the color-changing system to prevent it from directly contacting nylon 6 and affecting the material properties, while allowing small molecular aging products to diffuse in and react.
[0035] The stabilizer is a hindered amine light stabilizer (HALS). Adding a HALS can delay the oxidation of the oxidation indicator itself, ensuring that the signal reflects the true degree of aging rather than premature discoloration. HALS are commercially available products, often named "HALS" or a specific model. Beijing Tiangang Additives Co., Ltd. offers light stabilizers such as HS-944 and HS-770, clearly labeled "Hindered Amine Light Stabilizers (HALS)," suitable for materials such as polyolefins and nylon.
[0036] In this embodiment, the method for preparing the aforementioned aging-responsive color-changing material includes the following steps:
[0037] Step 1. Loading of oxidation indicator (mesoporous silica as carrier): Immerse mesoporous silica nanoparticles with a pore size of 3-5 nm in an alkaline aqueous solution of tetramethyl-p-phenylenediamine and potassium ferrocyanide, and ultrasonically disperse for 15-20 minutes (ultrasonic power ≥ 200 W); let it stand for 2 hours to allow adsorption equilibrium, and then vacuum dry at 60°C to remove the solvent to obtain nanoparticles loaded with oxidation indicator.
[0038] Step 2, raw material ratio (parts by mass): alkaline aqueous solution of tetramethyl-p-phenylenediamine and potassium ferrocyanide: 100 parts; silica loaded with oxidation indicator: 3-5 parts; hindered amine light stabilizer: 0.5-2 parts.
[0039] Step 3, dehydration: add alkaline aqueous solution of tetramethyl-p-phenylenediamine and potassium ferrocyanide and hindered amine light stabilizer into the reaction kettle, dehydrate under negative pressure at 110-120° C. for 5-20 minutes, and stir at 200-300 rpm.
[0040] Step 4, mixing: add the silica loaded with the oxidation indicator into the kettle, and stir for 2 minutes until uniform, thereby obtaining the aging-responsive color-changing material.
[0041] The aforementioned aging-responsive color-changing material is evenly dispersed onto the surface of nylon 6 by spraying, with a thickness of 0-200μm and an addition level of 0.3-0.8wt% (based on the mass of the nylon). The sprayed color-changing material is neither too thick (exceeding 200μm) nor too thin (at least 0.3wt%). When nylon 6 undergoes oxidative aging, the material's color gradually changes from white to blue, with a color difference of ΔE reaching 15-25, far exceeding the threshold for visual recognition (ΔE>3).
[0042] In this embodiment, when nylon 6 undergoes oxidative aging, the color change of the material can only serve as the basis for a qualitative evaluation of the aging of nylon 6. To achieve a more accurate quantitative evaluation of aging, the present invention develops a composite conductive film. The base material of the composite conductive film is carbon nanotubes (CNTs), and the thickness of the composite conductive film is about 50 μm. The surface layer of nylon 6 is melted and softened under hot pressing conditions, and a grid-like carbon nanotube (CNT) is placed 0.2 mm below the surface of the nylon 6 component by hot pressing, thereby covering key detection areas, such as locations exposed to long-term sunlight exposure, long-term immersion in seawater, and mechanical force and friction.
[0043] It should be noted that the composite conductive film is hot-pressed beneath the surface of the nylon 6 component. The depth of the hot pressing is not uniform, so the thickness of the intermediate layer includes the depth of the hot pressing beneath the nylon 6 component and the thickness of the composite conductive film, which is within the range of 200-250μm. When nylon 6 oxidizes, the resistance of the carbon nanotube (CNT) network changes.
[0044] The composite conductive film has the following characteristics: Resistance variation range: 10 4 -10 6 Ω corresponds to an oxidation degree of 0-90%. Signal reading: Resistance can be measured using a simple multimeter. Specifically, nanotubes (CNTs) mainly include multi-walled carbon nanotubes (MWNTs), thin-walled carbon nanotubes (TWNTs), and single-walled carbon nanotubes (SWNTs). Thin-walled carbon nanotubes (TWNTs) are preferred in this invention. Parameters include an outer diameter of 3–5 nm, a length of 5–30 μm, a purity >90%, and a conductivity >100 S / cm.
[0045] Example 2:
[0046] Since the color change is mainly caused by surface oxidation and the generation of chromophores. The color difference ΔE is positively correlated with the degree of aging. Experiments show that after 2-3 years of outdoor exposure, the material enters a significant degradation stage when ΔE>5; the resistance change reflects the degradation of the internal structure of the material (such as molecular chain breakage and increase in hydrophilic groups). The resistance change rate (dR / R) under high temperature and high humidity environment is related to the degree of oxidation. When the resistance change rate exceeds 10%, it indicates that the matrix-fiber interface is weakened and the mechanical properties are significantly reduced. Based on these studies, this embodiment provides a method for detecting and evaluating nylon 6 aging under a marine environment. The system described in Example 1 is used to normalize the color and resistance parameters to construct a comprehensive aging index (CAI):
[0047] (1)
[0048] Where, , is the weight coefficient (needs to be calibrated experimentally, recommended , , because the color change is more intuitive). : Color difference threshold ( =5, corresponding to the significant degradation point). : Resistance change threshold (take ). is the resistance change; is the initial resistance value.
[0049] Combining formula (1) and existing standards, the evaluation criteria based on CAI are given: CAI < 0.5: slight aging (reversible stage); 0.5 ≤ CAI < 1.0: moderate aging (maintenance required); CAI ≥ 1.0: severe aging (replacement required).
[0050] The above description is only a specific embodiment of the present invention, and the protection scope of the present invention is not limited thereto. Any person familiar with the technology can understand and think of any changes or replacements within the technical scope disclosed by the present invention, which should be included in the scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for detecting and evaluating aging of nylon 6 in a marine environment, characterized in that: The method normalizes the color and resistance parameters to construct a comprehensive aging index CAI, which is expressed as: (1) Where, , represents the weight coefficient, , ; represents the color difference threshold, =5; represents the resistance change threshold, ; Indicates the resistance change; Indicates the initial resistance value; The evaluation criteria of CAI are: CAI < 0.5: mild aging; 0.5 ≤ CAI < 1.0: moderate aging; CAI ≥ 1.0: severe aging.
2. A system for implementing the method for detecting and evaluating nylon 6 aging in a marine environment according to claim 1, characterized in that: It includes nylon 6 as the core layer, aging-responsive color-changing material as the surface layer, and an intermediate layer located between the core layer and the surface layer, wherein the core layer is pure nylon 6 or glass fiber reinforced nylon 6, which is used to maintain mechanical properties; the intermediate layer has a thickness of 200-250μm, and the composite conductive film is transferred to 0.2mm below the surface of the nylon 6 component by hot pressing; the surface layer has a thickness of 0-200μm, which is achieved by spraying the aging-responsive color-changing material solution.
3. The system according to claim 2, characterized in that The aging-responsive color-changing material is composed of the following components: an oxidation indicator, a nanocarrier, and a stabilizer, wherein the oxidation indicator is an alkaline aqueous solution of tetramethyl-p-phenylenediamine and potassium ferrocyanide; the nanocarrier is mesoporous silica nanoparticles; and the stabilizer is a hindered amine light stabilizer.
4. The system according to claim 3, characterized in that The pore size of the silicon dioxide nanoparticles is 3-5 nm.
5. The system according to claim 4, characterized in that The preparation method of the alkaline aqueous solution of tetramethyl-p-phenylenediamine and potassium ferrocyanide is as follows: potassium ferrocyanide and tetramethyl-p-phenylenediamine are dissolved in the alkaline aqueous solution in sequence, the concentration of potassium ferrocyanide is 0.2 mol / L, the concentration of tetramethyl-p-phenylenediamine is 0.2-0.4 mol / L, the reaction temperature is normal room temperature, and the reaction time is 1-3 hours.
6. The system according to claim 5, characterized in that The method for preparing the aging-responsive color-changing material comprises the following steps: Step 1: Using mesoporous silica as a carrier and loading an oxidation indicator: Mesoporous silica nanoparticles with a pore size of 3-5 nm are immersed in an alkaline aqueous solution of tetramethyl-p-phenylenediamine and potassium ferricyanide, and ultrasonically dispersed for 15-20 minutes. The mixture is allowed to stand for 2 hours to allow adsorption equilibrium, and then vacuum-dried at 60°C to remove the solvent, thereby obtaining nanoparticles loaded with the oxidation indicator. Step 2, raw material mass ratio: alkaline aqueous solution of tetramethyl-p-phenylenediamine and potassium ferrocyanide: 100 parts; silica loaded with oxidation indicator: 3-5 parts; hindered amine light stabilizer: 0.5-2 parts; Step 3, dehydration: add alkaline aqueous solution of tetramethyl-p-phenylenediamine and potassium ferrocyanide and hindered amine light stabilizer into the reaction kettle, dehydrate under negative pressure at 110-120°C for 5-20 minutes, and stir at 200-300 rpm; Step 4: Mixing: Add the silica loaded with the oxidation indicator into the kettle and stir for 2 minutes until the mixture is uniform.
7. The system according to claim 6, characterized in that The thickness of the aging-responsive color-changing material is 0-200 μm, and the addition amount is 0.3-0.8 wt%. When nylon 6 undergoes oxidative aging, the color of the material will gradually change from white to blue, and the color difference ΔE reaches 15-25, far exceeding the threshold ΔE>3 that can be identified by the naked eye.
8. The system according to claim 2, wherein: The basic material of the composite conductive film is carbon nanotubes, and the thickness of the composite conductive film is 50 μm.
9. The system according to claim 8, characterized in that The nanotube is one of multi-walled carbon nanotube, thin-walled carbon nanotube and single-walled carbon nanotube.
10. The system according to claim 9, characterized in that The carbon nanotubes are thin-walled carbon nanotubes with an outer diameter of 3-5 nm, a length of 5-30 μm, a purity of >90%, and a conductivity of >100 S / cm.
Citation Information
Cited By
Online identification method and system for adsorption kinetic parameters of imidazolium resin
CN121978320A
Online identification method and system for adsorption kinetics parameters of imidazolium resin
CN121978320B